2017
DOI: 10.1108/aaouj-01-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

The potential and challenges of MOOCs in Pakistan: a perspective of students and faculty

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The gap regarding online education between Western and Asian countries is obvious; in this context, Ahmed et al (2017, p. 102) found “Western online education platforms are undoubtedly valuable but they lack our domestic cultural needs and practices.” This cultural difference can be convincingly illustrated by the four-dimensional model of cultural differences (see Table 1) developed by Hofstede (1986).…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…The gap regarding online education between Western and Asian countries is obvious; in this context, Ahmed et al (2017, p. 102) found “Western online education platforms are undoubtedly valuable but they lack our domestic cultural needs and practices.” This cultural difference can be convincingly illustrated by the four-dimensional model of cultural differences (see Table 1) developed by Hofstede (1986).…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…The qualitative reports in the questionnaire identified some factors as inhibiting use of the MOOC, including the limited internet access in some regions, especially in remote areas. Limited internet access as a drawback of the use of MOOCs for CME has been similarly reported in other developing countries [15,17,18]. The use of varied forms of content, not only video lectures that use large internet bandwidth, was helpful.…”
Section: Discussionmentioning
confidence: 68%
“…Studies (Mehall, 2021;Wu et al, 2010) have shown that the absence of face-to-face interaction and lack of classroom environment are the major obstacles that hinder the successful implementation of e-learning systems. Similarly, a study (Naveed et al, 2017) Another study (Kamba, 2009) proficiency in the English language, cultural beliefs, and students' inadequate access to the internet and computer (Ahmed et al, 2017;Mumtaz et al, 2021). This low proficiency in the English language and lower technological skills result in a lack of self-motivation among students regarding using e-learning systems.…”
Section: Barriers Affecting the Implementation Of E-learningmentioning
confidence: 99%